The Implementation of Hanging Board Media in Improving Mathematics Learning Outcomes on Number Sequence Material for Grade 2 Students at MI Miftahul Ulum - Febriani, Lia Putri; Aisyah, Nurul (Kepompong Children Centre Journal, 2025)
This study aims to improve mathematics learning outcomes on number sequence material for Grade 2 students at MI Miftahul Ulum by implementing hanging board media. This classroom action research was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were second-grade students of MI Miftahul Ulum. Data were collected through observation, tests, and documentation. The study results indicate that using hanging board media can enhance students’ learning outcomes in mathematics. Improvements were observed across the learning cycles, with a notable increase in student engagement, participation, and motivation during the learning process. The hanging board media proved effective in helping students grasp the concept of number sequences more concretely and interestingly. This research contributes to developing innovative learning media for primary mathematics education, especially making abstract mathematical concepts more accessible to young learners through visual and interactive approaches.